An overview and proposal for analysis of the effectiveness of human factors in Dubai e-banking system - Abdulghafor, Rawad; Jasim, Aiysha; Zeki, Akram M. (Allied Academies, 2017)
Nowadays, every transaction is done electronically through various e-channels like, ATMs, credit/debit cards, internet banking, mobile banking, telebanking, EFTs, etc. There are many factors that attract people to use the internet banking and encourage increasing the customers for the bank. In this paper, the human factors (factors from e-banking customers) are extracted by extensive literature review then statistical analysis is to be suggested to measure these factors. The study is to be conducted in Dubai and the valid responses are to be analyzed by Partial least squares (PLS) technique of analysis. Independent samples Test are to be carried out to find the effect of customers familiar with e-banking factors. The analysis is to reveal security awareness among the customers of e-banking in Dubai.